Improving Family Financial Literacy and Behavior through Mentoring and Counseling for Mothers Empowerment and Family Welfare: Improving Family Financial Literacy and Behavior through Mentoring and Counseling for Mothers Empowerment and Family Welfare - Nursiam; Kusumawati, Annisa Fitriana; Zana Zein Hardimanto; Putri Linggasari Sofi; Rafi Amani Muflih Rahardi; Pinnacle Ferdyamin; Ahmad Syihan Setiawan; Kenji Satriatama; Sri Winarni; Ghiffari Naufal Fauzan (Universitas Muhammadiyah Surakarta, 2025)
This community service program aims to improve financial literacy and management skills among members of the Sidomulyo and Banyuanyar Family Welfare Movements (PKK) who face challenges in managing household finances, such as a tendency to get into debt and an inability to plan properly. Excessive debt and uncontrolled spending often lead to reliance on informal loans and financial difficulties. To address these challenges, the program offers training covering the basics of financial management, debt management, the importance of saving and investing, and long-term financial planning. Methods used in the program include interactive lectures, simulations, individual mentoring, and the use of accessible financial technology. Through mentoring and counseling that emphasized adaptive financial management such as flexible savings strategies according to income conditions, recording daily expenses, and strengthening understanding of debt management, participants demonstrated increased awareness and understanding of more planned financial management.